2015
DOI: 10.1186/s12864-015-1954-x
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis reveals the extent of EAV-HP integration in domestic chicken

Abstract: BackgroundEAV-HP is an ancient retrovirus pre-dating Gallus speciation, which continues to circulate in modern chicken populations, and led to the emergence of avian leukosis virus subgroup J causing significant economic losses to the poultry industry. We mapped EAV-HP integration sites in Ethiopian village chickens, a Silkie, Taiwan Country chicken, red junglefowl Gallus gallus and several inbred experimental lines using whole-genome sequence data.ResultsAn average of 75.22 ± 9.52 integration sites per bird w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 50 publications
(67 reference statements)
0
12
0
Order By: Relevance
“…However, while the biological functions of MYCL is still being studied (Brägelmann et al, 2017 ), both TRIT1 and MYCL genes have been linked to the maintenance of tumors (Smaldino et al, 2015 ; Brägelmann et al, 2017 ). All three genes may be of importance in both domestic and the wild ancestor; HPCAL4 in relation to behavioral characteristics, TRIT1 and MYCL in relation to adaptation to retrovirus infection in particular to virus causing tumors (e.g., leukosis and Marek virus) commonly affecting chicken (Cheng et al, 2010 ; Wragg et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, while the biological functions of MYCL is still being studied (Brägelmann et al, 2017 ), both TRIT1 and MYCL genes have been linked to the maintenance of tumors (Smaldino et al, 2015 ; Brägelmann et al, 2017 ). All three genes may be of importance in both domestic and the wild ancestor; HPCAL4 in relation to behavioral characteristics, TRIT1 and MYCL in relation to adaptation to retrovirus infection in particular to virus causing tumors (e.g., leukosis and Marek virus) commonly affecting chicken (Cheng et al, 2010 ; Wragg et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…EAV-HP is an ancient endogenous transcriptional virus that persists in modern poultry, which is inseparable with the high pathogenic avian leukosis virus subgroup-J . Wragg et al. (2015) analyzed several poultry genomes and found that EAV-HP had approximately 75 integration sites on each bird, and the related genes revealed that it may be involved in immune regulation and cell adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the numerous point mutations, deletions and insertions in the sequences, EAV-HP is likely a helper virus that inactivates viral gene products. To date, none of the proviruses have been observed to produce infectious virions [42]. Thus, we assume that the EAV-HP genome is a safe harbor for exogenous gene integration that has little effect on functional gene expression in the chicken genome.…”
Section: Discussionmentioning
confidence: 99%